The Effectiveness of Juvenile Correctional Facilities: Public versus Private Management - Patrick Bayer; David E. Pozen (Yale University, Economic Growth Center, 2003)
This paper uses data on juvenile offenders released from correctional facilities in Florida to explore the effects of facility management type (private for-profit, private nonprofit, public state-operated, and public county-operated) on recidivism outcomes and costs. The data provide detailed information on individual characteristics, criminal and correctional histories, judge-assigned restrictiveness levels, and home zipcodesallowing us to control for the non-random assignment of individuals to facilities far better than any previous study. Relative to all other management types, for-profit management leads to a statistically significant increase in recidivism, but, relative to nonprofit and state-operated facilities, for-profit facilities operate at a lower cost to the government per comparable individual released. Costbenefit analysis implies that the short-run savings offered by for-profit over nonprofit management are negated in the long run due to increased recidivism rates, even if one measures the benefits of reducing criminal activity as only the avoided costs of additional confinement.
Keywords: H0; H1; H4; K0; K4; 330; Juvenile Crime; Juvenile Correctional Facilities; Recidivism; Prison Privatization; Provision of Public Goods: Nonprofit; For-profit; Public; Jugendkriminalität; Strafvollzug; Nonprofit-Organisation; Privatwirtschaft; Privatisierung; USA